Approaches to maximise the utilisation of residues from thermal conversion of oil palm waste. - Ukanwa, Kalu Samuel (Cranfield University, 2020)
Palm oil processing generates enormous volume of waste, which can be used as a feedstock in thermal processing. Subsequently, these can be valuable in the production of activated carbon (AC) and soil amelioration. The production of AC often results in secondary contamination through activating agents. This prompts the necessity for a non-toxic activating agent for high quality production of high adsorptive AC. Therefore this research aims to assess and determine the optimum route for efficient utilisation of biowaste from thermal conversion process of palm oil residues in producing activated carbon and soil amelioration by evaluating the impact of the selected utilisation techniques. In the production process, energy demand and process duration have influence on the efficiency of AC; therefore, an appropriate design configurations and parameter selection are required to achieve an anticipated yield. AC was produced by microwave and conventional techniques through pyrolysis. The feedstock was also used in combustion and the thermal residues were applied in agricultural soil and crop yield relative to application rate was assessed on Habanero chili pepper. Therefore, the requisite to quantify the processes, which include appropriate assessment of the technology and economic performance. The accomplishment of the project overall aim was dependent on the design of a microwave system for efficient biomass pyrolysis. The process also evaluated the microwave interaction with reactors implemented to produce AC from mixed oil palm waste, using Trona ore as an activating agent. The AC was analysed to determine the effectiveness of Trona ore for activation using Fourier infrared spectrometry, Brunauer-Emmett-Teller (BET) analyser and scanning electron microscope. The oil palm waste ash was applied to the soil. The optimum outcome of the microwave assisted technique for combine palm waste (CPW) was obtained at 600 W, BET surface area (SBET) is 980 m²/g compared to 920 m²/g from a conventional technique; total volume (Vtotal) 0.865 cm³/g; mean pore diameter 2.2 nm and AC yield is 42%. Therefore, this study additionally identifies the need for an even distribution of electromagnetic waves within the reactor during activation to ensure uniformity of AC. It also proposes that the design of a composite reactor for an industrial production of AC is necessary to enable heterogeneous waste stream of the process. For ash application, the physiological development and crop yield were measured. The combine maximum yield for both sites were 49 t/ha/first season and 71.8 t/ha/second season, occurred at 8 t/ha treatment plot against the control plot with 1.3 t/ha/first season and 0.7 t/ha/second season. The interaction between oil palm waste ash and soil, improved agronomic efficiency of Habanero chilli pepper by 66-69% and Scoville value by 3.52%. These utilisation routes (AC production and ash to soil) were further integrated for economic and technological benefits using Aspen plus Economy. The processes have 16-17% return on investment for the 8-9 year payback period. This study therefore concluded that thermal residues of oil palm waste are useful in the production of high quality AC and also has rich effect on agricultural soil.
Keywords: Activated carbon; adsorption; porus material; kinetic model; economic assessment; soil amelioration